Social Vulnerability Changes and Sustainable Development in The Flooded Industrial Complex Area - Nakasu, Tadashi; Bula-Or, Ruttiya; Anantsuksomsri, Sutee; Positlimpakul, Korrakot (European Publisher, 2019)
Focusing on disaster risk management of enterprises in industrial complex areas is significant for learning from disasters; however, there has not been much exploration of longer and social-oriented perspectives. Therefore, the study detailed in this paper sought to investigate systematically the changes before and after the 2011 flood disaster in the vulnerability of Ayutthaya province, primarily focusing on the social vulnerability gaps and changes in the district, including areas that both include and do not include industrial parks/estates, in order to examine sustainability. Field surveys and statistical analyses were undertaken to explore this research. As a result, the study found: 1) Phra Nakhon Si Ayutthaya (PNSA) is the most vulnerable district; 2) the east side of Ayutthaya, which does not include industrial parks/estates, indicates high social vulnerability; 3) Bang Pa-in district, which has two industrial parks/estates, became more vulnerable after the disaster with a growing high susceptibility and exposure tendency. The study recommends that updated flood and vulnerability risk information be shared and active collaboration be undertaken among stakeholders, including central and local government administrations, infrastructure providers, private enterprises and communities, not only during disasters but also before and after the disaster in order to attain sustainable development in the industrial complex area. This research was conducted as a part of the Science and Technology Research Partnership for Sustainable Development (SATREPS) (Japanese government ODA) project.